Neuroimaging in Visual Snow - A Review of the Literature - Raviskanthan, Subahari; Ray, Jason C.; Mortensen, Peter W.; Lee, Andrew G. (Frontiers in Ophthalmology, 2022)
Since the first description of visual snow syndrome (VSS) in 1995, there has been increasing interest particularly within the past 5-10 years in phenotyping the condition and differentiating it from conditions such as migraine with aura and hallucinogen persisting perception disorder. Structural and functional neuroimaging has provided valuable insights in this regard, yielding functional networks and anatomical regions of interest, of which the right lingual gyrus is of particular note. Various modalities, including functional magnetic resonance imaging (fMRI), positron emission tomography (PET), and single photon emission computed tomography (SPECT), have all been studied in patients with visual snow. In this article, we conduct a comprehensive literature review of neuroimaging in VSS.